New measurement approaches to identifying spatial concentrations of poor and low-income households in German city regions; Neue Messansätze zur Detektion räumlicher Konzentrationen armer und einkommensschwacher Haushalte in deutschen Stadtregionen - Stefan Fina; Julian Schmitz; Sabine Weck; Carmella Pfaffenbach; Diane Dobusch (Raumforschung und Raumordnung / Spatial Research and Planning, 2024)
The question of whether 21st-century urbanization dynamics are leading to a suburbanization of poverty in Western city regions has been on the agenda of spatial researchers and housing policymakers for over a decade now. Persistent reurbanization trends are putting increased pressure on inner-city housing markets, resulting in affordability problems for low-income households. Evidence from the US and the UK shows that financing mechanisms in the real estate sector were severely disrupted in the aftermath of the financial crisis in 2009 and subsequent years, with many households losing their homes and being forced to move. Though social security systems and social housing policies generally have a moderating effect, they vary widely across Western countries. Against this background, this paper presents three spatial observation methods tailored to the spatial analysis of poverty concentrations in Germany. The methods are based on three popular conceptualizations of poverty: material poverty, relative poverty, and the concept of neighbourhood deprivation. The main novelty presented in this paper is a cold-spot analysis of purchasing power in 33 city regions using interactive map visualizations and complemented by socioeconomic indicators. Expert feedback verifies the validity of the approach which addresses a "blind spot" in assessing poverty in Germany, where many low-income households are increasingly exposed to risks of poverty despite not qualifying for social benefits. – – Seit über einem Jahrzehnt gehen Raumwissenschaftler der Frage nach, ob die Urbanisierungsdynamiken des 21. Jahrhunderts zu einer Suburbanisierung von Armut in westlichen Stadtregionen führen. PersistenteTrends der Reurbanisierung verstärken den Druck auf innerstädtische Wohnungsmärkte,einkommensschwache Haushalte sind so erheblichen Engpässen für bezahlbares Wohnen ausgesetzt. Forschungsergebnisse aus den Vereinigten Staaten und Großbritannien verweisen auf die Nachwirkungen der Finanzmarktkrise 2009 und ihre disruptiven Auswirkungen auf die Eigenheimfinanzierung, als in der Folge zahlreiche Haushalte umziehen mussten.Sozialpolitik und soziale Wohnraumversorgung sind zwar generell dazu konzipiert, diese Effekte nach Möglichkeit abzufedern, sie funktionieren in den westlichen Industrieländern allerdings sehr verschieden. In diesem Zusammenhang präsentiert der vorliegende Beitrag drei Ansätze zur räumlichen Analyse von Armutskonzentrationen in Deutschland. Die Messmethoden basieren auf drei verbreiteten Armutskonzepten: der materiellen Armut, der relativen Armut und dem Konzept der benachteiligenden Lage. Die zentrale Neuerung des Beitrags besteht in einer Cold-Spot Analyse der Kaufkraft in 33 Stadtregionen, die als interaktive Kartendarstellung im Internet verfügbar ist und durch sozioökonomische Indikatoren ergänzt wird. Rückmeldungen aus Expertengesprächen bestätigen die Passfähigkeit der Messmethode im Hinblickauf einen "blindenFlecken" in der deutschen Armutsforschung. Dieser betrifft eine hohe Zahl einkommensschwacher Haushalte,die zwar keine Sozialhilfe erhalten, aber dennoch zunehmend armutsgefährdet sind.
Keywords: 710; affordable housing; cold-spot analysis; low-income households; Measurement approaches; spatial poverty concentrations; suburbanization; Messmethoden; Suburbanisierung; räumliche Armutskonzentration; einkommensschwache Haushalte; bezahlbares Wohnen; Cold Spot Analyse